HIV Epidemic in Libya: Identifying Gaps - A. Hamidi (SAGE Publishing, 2021)
Background: HIV (human immunodeficiency virus) and AIDS (acquired immunodeficiency syndrome) became a public issue in Libya after the infection of 400 children in El-Fatih Hospital in 1988. Due to the civil war, social and religious barriers, HIV prevalence is hard to establish, but it is generally believed to be increasing. Objective: This review (a) assesses the size and scope of the available literature on the HIV epidemic in Libya; and, (b) identifies the nature and extent of research conducted to date. Methods: A comprehensive search was performed using PubMed, Medline, Web of Science, ScienceDirect, Scopus, Academic Search Ultimate, Cochrane Library and Google Scholar. Primary research studies and official reports that are exclusively on Libya published during 1988−2021 were considered. Results: In total 25 studies were included: Ten primary research studies, four online news articles, six Government reports, one letter to the editor, one manuscript, three online databases Conclusion: Despite the low-quality data, the literature suggests there is an increase in HIV infection rates in Libya. Culturally sensitive research on sexual activities, women, HIV preventative methods and attitudes of the Libyan public will assist in developing an effective National AIDS Programme, reducing HIV stigma, supporting People Living with HIV (PLHIV) and decreasing infection rates.